COMMUNICATION STRATEGY OF THE VILLAGE HEAD IN BUILDING GOOD GOVERNANCE IN NAGORI TANJUNG PASIR, TANAH JAWA SUB-DISTRICT, SIMALUNGUN REGENCY - Siallagan, Nursistani; Syahminan, Mhd (Journal Analytica Islamica, 2025)
This study aims to examine the communication strategies implemented by the Village Head of Nagori Tanjung Pasir, Tanah Jawa District, Simalungun Regency in building good governance at the village level. Using a qualitative descriptive method, data were collected through observation, interviews, and documentation involving the village head and local residents. The findings indicate that the village head applies open, participatory, and responsive communication strategies by utilizing both formal and informal media such as local leaders (gamot), village information boards, and personal social media platforms. The implementation of good governance principles is reflected in active public participation, transparent information dissemination, accountable aid distribution based on objective data, and effective public service delivery. The communication strategies employed have strengthened public trust and accelerated the realization of fair, transparent, and community-oriented governance in the village.